Trusts in hybrid mismatch arrangements: does the OECD BEPS action plan adequately address the unique attributes of trusts? - de Koker, Lori Adiella (My University, 2022)
This paper assesses whether the Organization for Economic Co-operation and Development (OECD) has effectively neutralised trust-based hybrid mismatch arrangements with the recommendations incorporated in Action 2 of the Base Erosion and Profit Shifting (BEPS) Action Plan. The OECD employed a consequentialist approach to hybrid mismatch arrangements, focusing on mending the outcomes of mismatch transactions as opposed to the source of the mismatches. Since trusts comprise several distinctive attributes, such as conflicts of attribution, which may result in mismatches, the OECD encountered difficulties in addressing trust-based mismatched systematically through the consequentialist approach. Slow convergence from the international community represents a further threat to the success of the OECD initiative. This paper will explore the adoption of the Action 2 recommendations concerning trustbased mismatches within the international community, placing a focus on South Africa. Possible alternatives to address hybrid mismatch arrangements will also be assessed.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce in Taxation to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2021
Keywords: UCTD; Base Erosion and Profit Shifting; OECD; Action Plan; Action 2; Hybrid Mismatch Arrangement; SDG-8: Decent work and economic growth